Assembly of propylene glycol alginate/β-lactoglobulin composite hydrogels induced by ethanol for co-delivery of probiotics and curcumin. (15th February 2021) - Su, Jiaqi; Cai, Yongjian; Zhi, Zijian; Guo, Qing; Mao, Like; Gao, Yanxiang; Yuan, Fang; Van der Meeren, Paul
Highlights: A hydrogel-based delivery system was fabricated from food-grade components. A dendritic network was formed by filamentous PGA molecules densely closed by β-lgNPs. The composite hydrogel was effective at sustaining the release of curcumin. The encapsulated probiotics exhibited a high survival rate upon long-time storage. Abstract: Probiotics and curcumin can exhibit synergistic biological activities on the basis of a gut-brain axis, but are sensitive to environmental conditions, making it a challenge for their co-utilization. To meet the demand for high efficiency and convenience, both probiotics and curcumin were encapsulated within a propylene glycol alginate-based hydrogel delivery system, which was assembled using an ethanol-induced approach. The composite hydrogel was effective at sustaining the release of curcumin and protecting LGG cells in simulated gastrointestinal tract conditions. Moreover, it could also largely reduce the chemical degradation of curcumin and increase the survival of LGG during light exposure and long-term storage: up to 91.3 % of curcumin and 9.72 log CFU cm −3 remained present throughout 4 weeks of storage. Results in this work demonstrate a low-energy and green approach to assemble a composite hydrogel with remarkable biocompatibility, which is considered as a desired delivery vehicle for co-delivery of probiotics and curcumin.